A linha de cuidado do idoso nas redes assistenciais de Fortaleza-CE : visão dos gestores - Bruno, Carla Targino da Silva (2009)
Introduction As a result to the population aging, changes in demographic and epidemiological profile is public health problem, entailing the need to develop health policies and practices for the population. Fortaleza is a city of two and a half million inhabitants, of which 7.48% are elderly. The assessment of how the care for the elderly occurs in health assistance networks in Fortaleza produces information that can support the decision taken by the municipal government. Purpose Understanding how the way of caring for the elderly takes place in five health care networks in Fortaleza, in the perception of managers acting in this scenario. Methodology A qualitative study with descriptive approach and focus group technique. The Discourse of the Collective Subject was used to organize the findings (LEFÉVRE, LEFÉVRE, 2006). Results In the Family Health assistance network (so called Estratégia Saúde da Família), the actions of health promotion and introduction of the recording book of the elderly as a working tool are highlighted. A significant unmet demand was observed due to the lack of specialized services in caring for the elderly in the Specialized assistance network. Specific care for the elderly was not observed in the Hospital assistance network, as he is seen as common user. In the Emergency assistance network, the removal is included as a priority, and in the hospital, the service applied is according to severity. In Mental Health assistance network, there is a psychosocial approach to community involvement and intersectorial coordination. Final considerations Among the main findings of this study is that the way of care for the elderly in the city of Fortaleza is still weak, where some strands are misaligned, or broken, compromising the continuity of service. Given the state of demographic transition and the demographic and epidemiological profile, there is a need for better integration of health care, anchored in the Family Health Strategy as well as the structuring of new specialized services, aiming to improve care for the elderly population of Fortaleza.